Aspergillus nidulans: A rare cause of brain abscess - Anita Kumari Gupta; Rajendra Singh Parihar; Saloni Garg; Satya Prakash Jindal (Apollo Medicine)
Fungal infections of the central nervous system (CNS) are rarely encountered, and their development largely depends on the interplay between the virulence factors of various fungi and host's immune system. Recently, there has been an increase in the number of organ transplants, chemotherapies, and human immunodeficiency virus infections due to which the incidence of fungal brain abscess has increased. Aspergillus species is the most common cause of fungal brain abscess and generally occurs in patients with hematological malignancies and cancer chemotherapy. More than 100 Aspergillus species are known, and among these, the most virulent one is Aspergillus fumigatus, but Aspergillus niger, Aspergillus flavus, and Aspergillus terreus (which is relatively amphotericin resistant) can also cause human disease. Aspergillus nidulans is a species of Aspergillus, which is more virulent than other species and has a high mortality rate. Here, we report a case of brain abscess in a 35-year-old young female caused by A. nidulans presenting with symptoms of cerebral mass effect. On potassium hydroxide examination, thin branched septate hyphae were seen, and culture showed the growth of A. nidulans. Given the complexity of the patients at risk and the diverse array of fungal pathogens, CNS fungal infection poses a considerable diagnostic and therapeutic challenge. Although outcome is frequently fatal in patients with fungal brain abscess, early diagnosis, and appropriate antifungal therapy may reduce morbidity and mortality.